2011
DOI: 10.1093/mp/ssr010
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the H+-ATPase from Dry and 5-Hours-Imbibed Maize Embryos in Its Native, Solubilized, and Reconstituted Forms

Abstract: Membranes undergo recovery upon rehydration in seed germination. Previous work has described that the plasma membrane H+-ATPase from maize embryos adopts two different forms at 0 and 5 h of imbibition. We investigated how the kinetics of these two forms could be affected by alterations in the plasma membrane (PM). In comparison to the 0-h, PMs from the 5-h imbibed embryos showed changes in glycerophospholipid composition, decrease in leakage, and increase in fluidity. Kinetics of the PM H+-ATPase from 0 and 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…3C). In this regard, it has been previously shown that the enzyme is already present at 0 h of imbibition with an activity differentially distributed throughout the embryo regions and that it is gradually replaced by different enzyme forms during the first 5 h of maize imbibition (Sánchez-Nieto et al , 1998; Enríquez-Arredondo et al , 2005; Sánchez-Nieto et al , 2011). Therefore, the increase in H + -ATPase activity at 18 h of imbibition was probably related to either the expression of a different isozyme, such as the MHA1 and MHA2 isoforms described in maize coleoptiles (Frías et al , 1996), or to post-translational regulatory mechanisms (Sondergaard et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3C). In this regard, it has been previously shown that the enzyme is already present at 0 h of imbibition with an activity differentially distributed throughout the embryo regions and that it is gradually replaced by different enzyme forms during the first 5 h of maize imbibition (Sánchez-Nieto et al , 1998; Enríquez-Arredondo et al , 2005; Sánchez-Nieto et al , 2011). Therefore, the increase in H + -ATPase activity at 18 h of imbibition was probably related to either the expression of a different isozyme, such as the MHA1 and MHA2 isoforms described in maize coleoptiles (Frías et al , 1996), or to post-translational regulatory mechanisms (Sondergaard et al , 2004).…”
Section: Resultsmentioning
confidence: 99%
“…However, this apparent dissimilarity could be explained by the appearance of new transporter isoforms. This is a common event that occurs in the progress of germination at early times (Andrianarison and Beneytout, 1992; Waterworth et al , 2000; Enríquez-Arredondo et al , 2005; Sánchez-Nieto et al , 2011). In the case of glucose (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A,B. Nevertheless, as several researchers have found that the kinetics of this enzyme may resemble cooperativity , our data were also analyzed with Eadie–Scatchard plots (Fig. C,D), which are ‘most sensititive to detect deviations from Michaelian behavior’ .…”
Section: Resultsmentioning
confidence: 99%
“…They suggested that, under physiological conditions, this site may be inaccessible to the substrate. Since then, several reports have provided evidence for the existence of different ATP‐binding sites in maize PM H + ‐ATPase, because the kinetic data suggested positive or negative cooperativity . In 1997, Roberts and Beaugé presented four models of substrate binding to PM H + ‐ATPase of maize, one of which they called a ‘minimal’ model, which does not require two binding sites to explain cooperativity.…”
Section: Introductionmentioning
confidence: 99%